2008
DOI: 10.1007/s10886-008-9554-8
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Foliar Quercetin in Natural Populations of White Birch (Betula pubescens) Increase with Latitude

Abstract: We investigated latitudinal and regional variations in the composition and concentrations of foliar flavonoids and condensed tannins in wild populations of white birch (Betula pubescens EHRH) in a large climatic transect in Finland. Concentrations of quercetin derivatives were correlated positively with latitude. By contrast, the concentrations of apigenin and naringenin derivatives were correlated negatively with latitude. These compound-specific latitudinal gradients compensated each other, resulting in no c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 50 publications
0
48
1
Order By: Relevance
“…Therefore, a higher allocation to defensive substances may be advantageous for plants growing in the warmer regions. However, some other studies did not find clear relationships between CT abundance and air temperature or latitude (Stark et al 2008). Adams et al (2009a) also showed only limited latitudinal trends in the concentrations of CT's, or other defensive compounds.…”
Section: Effects Of Climatic Conditions and Latitude On Ct Abundancementioning
confidence: 77%
“…Therefore, a higher allocation to defensive substances may be advantageous for plants growing in the warmer regions. However, some other studies did not find clear relationships between CT abundance and air temperature or latitude (Stark et al 2008). Adams et al (2009a) also showed only limited latitudinal trends in the concentrations of CT's, or other defensive compounds.…”
Section: Effects Of Climatic Conditions and Latitude On Ct Abundancementioning
confidence: 77%
“…Whereas leaf damage in the form of skeletonization induces changes in several flavonoid and isoflavonoid levels, feeding damage by the caterpillar V. cardui increased levels of one genistein glycoside, and feeding by the aphid A. glycines did not affect production of any compound. The increase in flavonoid content over time is to be expected as these compounds are induced by herbivore damage (Hagerman and Butler 1991), and by increased photooxidative stress, particularly in August when the aphid experiments were conducted (Stark et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the quality and quantity of phenolics are expected to differ among bilberry leaves growing in different parts of the country. Previous studies have shown that the phenolic content in juniper (Juniperus communis) and birch (Betula pubescens) leaves increases with latitude (Stark et al, 2008;Martz et al, 2009). However, although the effect of altitude and/or latitude on AC content of bilberry fruit has been previously shown (Lätti et al, 2008;Rieger et al, 2008), no data are available about changes of phenolic composition in bilberry leaves along large geographical gradients.…”
Section: Introductionmentioning
confidence: 98%